Counterfeit Purchase Intention of Fashion Brands: The Personal Values and Social Aspect of Consumers as Determinants - iin mayasari; Handrix Chris Haryanto; Iyus Wiadi; Adrian Azhar Wijanarko; Willy Abdillah (Gadjah Mada International Journal of Business, 2022)
Counterfeiting has become a growth industry in Indonesia. Consumers in Indonesia tend to find counterfeit products very easily, especially fashion products. The aim of this quantitative study is to analyze personal values and social factors toward counterfeit items and the intention to purchase counterfeit goods in Indonesia, with a focus on fashion products. The study also aims at analyzing the influence of novelty seeking, integrity values, and status consumption on people’s attitudes toward counterfeit goods. Furthermore, this study also addresses the influence of perceived risk, information susceptibility, physical vanity, and vanity-achievement on the intention to purchase counterfeit products. One hundred and ninety-three respondents were included in our study after survey questionnaires had been distributed in Indonesia. The respondents were 19 to 44 years old, living in Jakarta, Tangerang, Bogor, Bekasi, Yogyakarta, Bandung, Medan, Jambi, Batam, Pekanbaru and Samarinda, all of which are larger cities in Indonesia. Data were analyzed using partial least squares. The results of the study showed that the attitude toward counterfeit items was the most important factor in the willingness to purchase counterfeit goods. Novelty seeking, integrity, status consumption, and information susceptibility were also important determinants of people’s attitudes toward counterfeit products. Perceived risk, physical vanity, and achievement vanity were found to have an insignificant relationship with the intention to purchase counterfeit products .  This study also has an impact on marketing strategies. One of them is marketers can offer very prestigious brands to reduce the trade in counterfeit luxury brands.